2004
DOI: 10.2320/matertrans.45.2232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pass Strain on Grain Refinement in 7475 Al Alloy during Hot Multidirectional Forging

Abstract: Effect of pass strain (Á") on grain refinement was studied in multidirectional forging (MDF) of a coarse-grained 7475 Al alloy at 490 C under a strain rate of 3 Â 10 À4 s À1 . Samples of rectangular shape were deformed up to accumulated strains of around 6 with subsequent changes in loading direction 90 from pass to pass. The pass strains in each compression (Á") were 0.4 and 0.7. The cumulative flow curves integrated by each compression exhibit significant work softening just after yielding, followed by appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…These methods can provide large amount of plastic deformation required for the occurrence of grain refinement and result in several important effects on the physical and chemical properties of metals and alloys [2]. It has been well documented in the recent works [1,3,[11][12][13][14][15]19,20,22,23] that strain localization that appears during SPD results in significant intrinsic structure instability associated with formation of deformation/microshear bands at relatively low strains. Their number and boundary misorientation increase with further deformation, leading to a full development of fine crystallite components at high strains.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…These methods can provide large amount of plastic deformation required for the occurrence of grain refinement and result in several important effects on the physical and chemical properties of metals and alloys [2]. It has been well documented in the recent works [1,3,[11][12][13][14][15]19,20,22,23] that strain localization that appears during SPD results in significant intrinsic structure instability associated with formation of deformation/microshear bands at relatively low strains. Their number and boundary misorientation increase with further deformation, leading to a full development of fine crystallite components at high strains.…”
Section: Introductionmentioning
confidence: 97%
“…Several SPD techniques, such as equal channel angular pressing (ECAP) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], accumulative roll bonding (ARB) [16,17] and multi-directional forging (MDF) [1,2,[18][19][20][21][22][23], are mostly used for processing of crystalline materials to produce ultra-fine-grained (UFG) structures. These methods can provide large amount of plastic deformation required for the occurrence of grain refinement and result in several important effects on the physical and chemical properties of metals and alloys [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This material on testing at a different orientation, (stage 2) the flow stress goes to 90 MPa. This is due to the accumulated strain (dislocation) because of the previous stage of compression, as explained by Sitdikov et al [20].…”
Section: Resultsmentioning
confidence: 94%
“…Due to the repeating rotation of the loading direction with deformation passes during MDF, cumulative strain applied from various directions is very significant for the evolution of grain structure and flow behavior of the materials subjected to deformation. A large number of investigations on MDF have indicated that microstructure change during MDF, especially grain refinement, can be controlled by various process factors, such as strain pass, deformation temperature, strain rate, alloying elements, second phase, etc [8][9][10][11][12][13]. Sitdikov et al have found that the grain size and its volume fraction in 7475 aluminum alloys during hightemperature multi-directional compression are obviously different from those subjected to uniaxial compression [14].…”
Section: Introductionmentioning
confidence: 99%